2007
DOI: 10.3354/meps329131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of predation by sea ducks on clam abundance in soft-bottom intertidal habitats

Abstract: Recent studies have documented strong, top-down predation effects of sea ducks on mussel populations in rocky intertidal communities. However, the impact of these gregarious predators in soft-bottom communities has been largely unexplored. We evaluated effects of predation by wintering surf scoters Melanitta perspicillata and white-winged scoters M. fusca on clam populations in soft-bottom intertidal habitats of the Strait of Georgia, British Columbia. Specifically, we documented spatial and temporal variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…If variation in prey quality affects habitat use patterns of predators, this may lead to variable prey depletion by habitat. There is a growing appreciation that sea ducks can have significant, top-down depletion effects on bivalves over winter (Guillemette et al 1996, Larsen & Guillemette 2000, Lewis et al 2007), which in turn might lead to temporal changes in availability of prey in preferred foraging habitats.…”
Section: Introductionmentioning
confidence: 99%
“…If variation in prey quality affects habitat use patterns of predators, this may lead to variable prey depletion by habitat. There is a growing appreciation that sea ducks can have significant, top-down depletion effects on bivalves over winter (Guillemette et al 1996, Larsen & Guillemette 2000, Lewis et al 2007), which in turn might lead to temporal changes in availability of prey in preferred foraging habitats.…”
Section: Introductionmentioning
confidence: 99%
“…During the three over-wintering periods, a total of 381 samples from these quadrats were collected, of which 43, 62 and 30 in meadows, 25, 29 and 55 in paddy fields and 47, 60 and 30 in the mudflats from the early, middle to late wintering stages, respectively (Gillespie and Kronlund 1999). The locations of the fall quadrats were not resampled in the spring (Lewis et al 2007). …”
Section: Habitat Surveymentioning
confidence: 99%
“…These impacts can alter prey availability for several months (Oliver & Slattery 1985), and thus we suggest that longer-term effects on many bottom-feeding animals may be important, even if direct feeding associations with gray whales are rare. Moreover, feeding by gray whales during their northward migration coincides with increasing energy needs of marine birds as they prepare for migration and reproduction, at the same time that typical winter foods may have declined (Lewis et al 2007). If numbers of Pacific gray whales were indeed far greater in the past as suggested by recent genetic analyses (Alter et al 2007), interactions such as the one reported here may have historically been major factors in the foraging strategies and trophic relations of a range of bottom-feeding vertebrates.…”
Section: Discussionmentioning
confidence: 99%